Predicting Standard Penetration Test (SPT-N) Value from Electrical Resistivity Result - Mohamed Raffek, Mohamed Ashnor (IRC, 2016)
Soil investigation is the first stage of the process in order to obtain the parameter of the soil and also to understand the behavior of the subsoil before building any civil structure. It is important for optimizing the cost and to avoid from overdesigning of the foundation. Standard Penetration Test is the conventional and destructive method currently being used to obtain the soil profile of the tested site in order to obtain the parameter and characteristic of the soil.